Mitochondrial DNA as a potential tool for early cancer detection - Parr Ryan L; Dakubo Gabriel D; Thayer Robert E; McKenney Keith; Birch-Machin Mark A (Human Genomics, 2006)
Abstract The recent surge in mitochondrial research has been driven by the identification of mitochondria-associated diseases and the role of mitochondria in apoptosis. Both of these aspects have identified mitochondrial analysis as a vital component of medical research. Moreover, mitochondria have been implicated in the process of carcinogenesis because of their vital role in energy production, nuclear-cytoplasmic signal integration and control of metabolic pathways. Interestingly, at some point during neoplastic transformation, there is an increase in reactive oxygen species, which damage the mitochondrial genome. This accelerates the somatic mutation rate of mitochondrial DNA. It has been proposed that these mutations may serve as an early indication of potential cancer development and may represent a means for tracking tumour progression. The purpose of this review is to explore the potential utility that these mutations may afford for the identification and monitoring of neoplasia and malignant transformation where appropriate body fluids or non-invasive tissue access is available for mitochondrial DNA recovery. Specifically, prostate, breast, colorectal, skin and lung cancers are discussed.